2008
DOI: 10.1590/s0100-67622008000100006
|View full text |Cite
|
Sign up to set email alerts
|

Hidrocondicionamento de Parkia pendula [Benth ex Walp]: sementes com dormência física de árvore da Amazônia

Abstract: RESUMO -O visgueiro é uma árvore neotropical de importâncias econômica e ecológica. Este estudo objetivou determinar o tempo de embebição e o teor de água de sementes de Parkia pendula necessários para ativar o metabolismo e aumentar o desempenho pelo condicionamento. Sementes armazenadas (2 anos) e não armazenadas (7 dias) foram comparadas. Após o desponte as sementes foram submersas em água a 15 ºC, por períodos de 4 a 28 h, para atingir o grau de embebição desejado (20, 40, 60, 80 e 90%). Em seguida, foram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 12 publications
0
4
0
5
Order By: Relevance
“…When set to soak for an extended period, the seeds may suffer irreversible damage to the membrane system, and consequent leaching of cellular contents that negatively affects germination. Similar to Brauna, Parkia pendula seeds do not seem to tolerate long periods of soaking, and a reduction in germinability and percentages of normal seedlings can be observed when soaked for 24 h after the heat treatment (Pinedo and Ferraz, 2008). These authors found that a soaking greater than 20% of their mass after about 4h significantly reduced the emergence of seedlings.…”
Section: Resultsmentioning
confidence: 85%
“…When set to soak for an extended period, the seeds may suffer irreversible damage to the membrane system, and consequent leaching of cellular contents that negatively affects germination. Similar to Brauna, Parkia pendula seeds do not seem to tolerate long periods of soaking, and a reduction in germinability and percentages of normal seedlings can be observed when soaked for 24 h after the heat treatment (Pinedo and Ferraz, 2008). These authors found that a soaking greater than 20% of their mass after about 4h significantly reduced the emergence of seedlings.…”
Section: Resultsmentioning
confidence: 85%
“…Combinations of probabilities of independent Student's t tests was done using the inverse Chi-square method [24,25].…”
Section: Data Analysesmentioning
confidence: 99%
“…Priming reduces germination time, improves emergence uniformity and vigor of seedlings. The controlled hydration of the seeds can be accomplished by hydropriming or through osmotic solutions (Pinedo & Ferraz, 2008).…”
Section: Introductionmentioning
confidence: 99%